(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This article tells about the need for educational activities to have stable attention from children, sharp mindfulness, independence qualities of workfulness and batartibility, serious changes that occur with the transition of children to schools, the need to prepare each punctuation for the new environment in their school in kindergartens school-age children are not one of all homogeneity of school education, reasons why some children Also, the readiness of children to study at school, the child to the stage of social maturity of an individual, the child does not rise spontaneously, by the age of seven, psychically further growth of children who go to school is carried out in the process of educational work carried out at school, in the family, psychological preparation for school education.